A arquitetura em concessionários de automóveis e o baixo impacto ambiental - Puente, Javier López (2009)
The proposal of this research is an approaching of the architecture production for car dealers in Brazil, its main characteristics and their study based under the aspect of buildings with low environmental impact. To achieve this objective a study of architectural projects were done through survey of building and projects published in relevant and specialized publications in Brazil. The guide lines, drawings, area guides and other materials for construction by vehicles manufactures, were developed by them, for the construction of facilities to its distributors, and in parallel was made a research along the main systems of environmental impact assessment, international and national development, for environmental and certification of buildings. Concluding with a discussion of results and technical proposals for the low environmental impact: comfort (thermal and environmental), control (light and sunlight); care for the environment, energy consumption reduction; orientation, recycling and reuse, natural ventilation and urban integration. In Appendix 1 are presented in Tables prepared for the assessment of buildings, as part of the issues of certification and LEED-NC (Leadership in Energy and Environmental Design - New Constructions) and AQUA (Alta Qualidade Ambiental), used to see whether the decisions of project could collaborate in the environmental impact reduction and in which percentage.Vehicles dealers abroad information were provided in Appendix 2, which have adopted different design decisions that can help reducing environmental impact. A research time line was presented in Appendix 3, giving the cut time, linked to the deployment of automotive industry in Brazil, covering the period from January 1999 to December 2008.